Combined contact force and local impedance dynamics during repeat atrial fibrillation catheter ablation - Alken, Fares-Alexander; Scherschel, Katharina; Kahle, Ann-Kathrin; Masjedi, Mustafa; Meyer, Christian (Frontiers in Physiology, 2022)
Background: Optimal lesion formation during catheter-based radiofrequency current (RFC) ablation depends on electro-mechanical tip-tissue coupling measurable via contact force (CF) and local impedance (LI) monitoring. We aimed to investigate CF and LI dynamics in patients with previous atrial fibrillation (AF) ablation who frequently present with heterogenous arrhythmia substrate. Methods: Data from consecutive patients presenting for repeat AF or atrial tachycardia ablation using a novel open-irrigated single-tip ablation catheter were studied. RFC applications were investigated regarding CF, LI and the maximum LI drop (∆LI) for evaluation of ablation efficacy. ∆LI > 20 Ω was defined as a successful RFC application. Results: A total of 730 RFC applications in 20 patients were analyzed. Baseline CF was not associated with baseline LI (R = 0.06, p = 0.17). A mean CF < 8 g during ablation resulted in lower ∆LI (<8 g: 13 Ω vs. ≥ 8 g: 16 Ω, p < 0.001). Baseline LI showed a better correlation with ∆LI (R = 0.35, p < 0.001) compared to mean CF (R = 0.17, p < 0.001). Mean CF correlated better with ∆LI in regions of low (R = 0.31, p < 0.001) compared to high (R = 0.21, p = 0.02) and intermediate voltage (R = 0.17, p = 0.004). Combined CF and baseline LI predicted ∆LI > 20 Ω (area under the receiver operating characteristic curve (AUC) 0.75) better compared to baseline LI (AUC 0.72), mean CF (AUC 0.60), force-time integral (AUC 0.59) and local bipolar voltage (0.55). Conclusion: Combination of CF and LI may aid monitoring real-time catheter-tissue electro-mechanical coupling and lesion formation within heterogenous atrial arrhythmia substrate in patients with repeat AF or atrial tachycardia ablation.